2003
DOI: 10.1182/blood-2003-03-0949
|View full text |Cite
|
Sign up to set email alerts
|

The kringle stabilizes urokinase binding to the urokinase receptor

Abstract: The structural basis of the interaction between single-chain urokinase-type plasminogen activator (scuPA) and its receptor (uPAR) is incompletely defined. Several observations indicated the kringle facilitates the binding of uPA to uPAR. A scuPA variant lacking the kringle (⌬K-scuPA) bound to soluble uPAR (suPAR) with the similar "on-rate" but with a faster "off-rate" than wild-type (WT)-scuPA. Binding of ⌬K-scuPA, but not WT-scuPA, to suPAR was comparably inhibited by its growth factor domain (GFD) and amino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 68 publications
(112 reference statements)
2
45
0
2
Order By: Relevance
“…48,49 More recently, it has been suggested that the uPA kringle stabilizes uPA binding to its receptor mediated by the amino-terminal growthfactor-like domain. 50 Our data demonstrate that PEG 1-48 inhibits, like ATF, the binding of uPA to its receptor, although it is missing the kringle domain. The use of recombinant uPA1-48 rather than proteolytically derived uPA4-43 may account for this difference.…”
Section: Discussionmentioning
confidence: 86%
“…48,49 More recently, it has been suggested that the uPA kringle stabilizes uPA binding to its receptor mediated by the amino-terminal growthfactor-like domain. 50 Our data demonstrate that PEG 1-48 inhibits, like ATF, the binding of uPA to its receptor, although it is missing the kringle domain. The use of recombinant uPA1-48 rather than proteolytically derived uPA4-43 may account for this difference.…”
Section: Discussionmentioning
confidence: 86%
“…Preparation of Wild Type and Mutant suPAR-Soluble urokinase plasminogen activator receptor (suPAR), isolated domains of suPAR (1-3), a fragment containing recombinant soluble suPAR domains 1 and 2 and 3 (S-D1, S-D2D3) and scuPA were prepared and expressed using the Drosophila Expression System (Invitrogen, Carlsbad, CA) according to manufacturer's instructions, as described previously (17,18). Isolated domains 1,2, and 3 of suPAR were prepared from wild type protein by sequential digestion with chymotrypsin and pepsin as previously reported (19).…”
Section: Methodsmentioning
confidence: 99%
“…To further reduce receptor heterogeneity resulting from differences in N-linked oligosaccharide structures, four of the five N-glycosylation sites of the suPAR WT were mutated (N162Q, N172Q, N200Q, and N233Q), and the resulting mutant was denoted suPAR 2345 (reported earlier in ref. 12). Both suPAR constructs were expressed in Drosophila Schneider's S2 cells and purified to homogeneity by combination of immunoaffinity chromatography and size-exclusion chromatography (data not shown).…”
Section: Protein Constructs and Heterologous Overexpressionmentioning
confidence: 99%